Stabilization of protein–protein interactions by small molecules - Giordanetto, Fabrizio; Schäfer, Anja; Ottmann, Christian (Drug discovery today, 2014)
•Protein–protein interactions (PPIs) are ever increasingly targets for drug discovery.•Targeted small molecule inhibition of PPIs has repeatedly been shown to be successful.•Targeted small molecule stabilization of PPIs is however an underexplored concept.•We review the current status of small molecule PPI stabilization as a fruitful concept. Protein–protein interactions (PPIs) are implicated in every disease and mastering the ability to influence PPIs with small molecules would considerably enlarge the druggable genome. Whereas inhibition of PPIs has repeatedly been shown to work successfully, targeted stabilization of PPIs is underrepresented in the literature. This is all the more surprising because natural products like FK506, rapamycin, brefeldin, forskolin and fusicoccin confer their physiological activity by stabilizing specific PPIs. However, recently a number of very interesting synthetic molecules have been reported from drug discovery projects that indeed achieve their desired activities by stabilizing either homo- or hetero-oligomeric complexes of their target proteins.